2014
DOI: 10.1200/jco.2014.32.3_suppl.577
|View full text |Cite
|
Sign up to set email alerts
|

Liver-directed therapies for colorectal cancer liver metastasis (CLRM): A Surveillance, Epidemiology, and End Results (SEER)-Medicare analysis.

Abstract: 577 Background: Oligometastatic CLRM comprises a distinct subset of stage IV colorectal cancer. Liver directed therapies (LDT) including surgery, ablation, radiation, and transarterial chemotherapy/embolization have been shown to improve cancer outcomes in smaller series. We sought to evaluate utilization of LDT and their impact on survival in patients with CLRM in a population-based database. Methods: We analyzed linked SEER-Medicare data. Eligible patients were ≥ 66 years, diagnosed between 1992-2009, carry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A recent study of 14,150 CRLM patients indicated that liver-directed therapies (LDT), including various ablative modalities, provided a strong survival benefit with a 26.9% 5 year overall survival achieved for those undergoing LDT and 7.5% who did not. 6 Although these local ablative techniques have made great strides in the palliative treatment of CRLM since their introduction, they are also limited by the size and location of tumors and have additional off-target effects such as bile duct or vascular injury due to the percutaneous insertion and nonspecific heating by ablative probes. Several clinical trials have evaluated the effectiveness of different ablation methods without a clear consensus.…”
mentioning
confidence: 99%
“…A recent study of 14,150 CRLM patients indicated that liver-directed therapies (LDT), including various ablative modalities, provided a strong survival benefit with a 26.9% 5 year overall survival achieved for those undergoing LDT and 7.5% who did not. 6 Although these local ablative techniques have made great strides in the palliative treatment of CRLM since their introduction, they are also limited by the size and location of tumors and have additional off-target effects such as bile duct or vascular injury due to the percutaneous insertion and nonspecific heating by ablative probes. Several clinical trials have evaluated the effectiveness of different ablation methods without a clear consensus.…”
mentioning
confidence: 99%